Welfare State Regimes and Social Determinants of Health in Europe - Johannes Pöschl; Katarina Valkova (The Vienna Institute for International Economic Studies (wiiw), 2015)
Abstract The aim of the paper is to identify social determinants of poor health when considering differences across countries and types of welfare states. In order to do so, we first perform a cluster analysis to classify countries into groups of welfare state models. The innovation of the paper is clustering method using the information about the actual redistributional effects and country health care expenditures instead of concentrating on country institutional arrangements. Thereafter, a logistic regression model is used to investigate the social determinants of poor health status in Europe, taking into account demographic and socioeconomic factors, indicators of relative poverty and finally environmental factors. Following the recent literature, we also apply an alternative estimation strategy and employ a multilevel logistic regression of individuals nested within countries with random intercept on the country level. The results show that, apart from age, inequality at the individual level is mostly determined by the education level, income and employment status as well as indicators of relative poverty. Environmental factors as well as other demographic characteristics such as migration or the marital status seem to matter less. Moreover, welfare state models play an important role in determining health inequalities across countries, even after controlling for a large number of socioeconomic characteristics at the individual level.
Keywords: H51; I18; 330; health; welfare regimes; health care expenditures; poverty; cluster analysis; multilevel analysis